A methodology for sketch analysis to support maintaining the design intent in virtual prototyping. (10th April 2010) - Mengoni, Maura; Germani, Michele
In the context of aesthetic products, one of the most important research issues with regard to the definition of methods and tools is to preserve the initial design intent along the whole product development process. Starting from a novel definition of freeform aesthetic feature, the present research aims at outlining an innovative methodology for design intent recognition and formalisation in terms of styling curves and CAD modelling strategies. Their identification is based on the analysis of freehand sketches evolution during creative design. The final result consists in an innovative procedure for virtual prototyping that enables shape modifications coherently with the design intent. The main scientific contribution is the implementation of an approach to extract meaningful aesthetic and functional information from sketches and to translate them into an operational procedure for virtual prototyping by adopting semiotic-based rules and descriptive models of creative design. The achieved methodology has been applied to support both the reverse engineering of freeform shapes and the direct modelling of virtual mock-ups.